Prevalencia de parásitos gastrointestinales en el ganado vacuno (boss taurus) en la parroquia de Guaytacama. - Quintuña Jácome, Jhonny Alexander (2022)
This research determines the prevalence of gastrointestinal parasites in cattle (Boss taurus) in the parish Guaytacama. According to the parasitic load and too the epidemiological map in order to identify the morphology of the eggs, analyzing the parasitic load in categories of age , sex, and the environment of the cattle herd of this parish The identification of gastrointestinal parasites was carried out with a coproparasitic examination through the flotation technique with a system count in crosses giving by field seen to 43 parasitized animals being the prevalence, from which the following results were obtained; With the highest prevalence of parasitic load in the parish, Oesophagostomum spp. (62.4%) followed by the parasitic genus Fasciola spp., (17.5%), Haemonchus spp., (11.5%), Cooperia spp., (3.3%) Trichostrongylus spp., (3.4%), Strongyloides spp. (1,9%). Oesophagostomum spp., is the leader of parasitic load in females over 3 years of age in the whole sector of Guaytacama due to the stabling environment of the cattle and thus producing gastrointestinal parasitic diseases due to food sanitation of the owners . Through this research study, it was possible to determine according to the epidemiological map that the environment of pastures and stagnant waters produce gastrointestinal parasites. Deworming campaigns should be carried out and more research study for the proper management of the cattle herd in the parish of Guaytacama.